The role of rheumatoid arthritis (RA) flare and cumulative burden of RA severity in the risk of cardiovascular disease. Issue 3 (30th January 2015) - Myasoedova, Elena; Chandran, Arun; Ilhan, Birkan; Major, Brittny T; Michet, C John; Matteson, Eric L; Crowson, Cynthia S
Abstract : Objective: To examine the role of rheumatoid arthritis (RA) flare, remission and RA severity burden in cardiovascular disease (CVD). Methods: In a population-based cohort of patients with RA without CVD (age ≥30 years; 1987 American College of Rheumatology criteria met in 1988–2007), we performed medical record review at each clinical visit to estimate flare/remission status. The previously validated RA medical Records-Based Index of Severity (RARBIS) and Claims-Based Index of RA Severity (CIRAS) were applied. Age- and sex-matched non-RA subjects without CVD comprised the comparison cohort. Cox models were used to assess the association of RA activity/severity with CVD, adjusting for age, sex, calendar year of RA, CVD risk factors and antirheumatic medications. Results: Study included 525 patients with RA and 524 non-RA subjects. There was a significant increase in CVD risk in RA per time spent in each acute flare versus remission (HR 1.07 per 6-week flare, 95% CI 1.01 to 1.15). The CVD risk for patients with RA in remission was similar to the non-RA subjects (HR 0.90, 95% CI 0.51 to 1.59). Increased cumulative moving average of daily RARBIS (HR 1.16, 95% CI 1.03 to 1.30) and CIRAS (HR 1.38, 95% CI 1.12 to 1.70) was associated with CVD. CVD risk was higher in patients with RA who spent more time in medium (HR 1.08, 95% CI 0.98 to 1.20) and high CIRAS tertiles (HR 1.18, 95% CI 1.06 to 1.31) versus lower tertile. Conclusions: Our findings show substantial detrimental role of exposure to RA flare and cumulative burden of RA disease severity in CVD risk in RA, suggesting important cardiovascular benefits associated with tight inflammation control and improved flare management in patients with RA.